2011
DOI: 10.1002/hep.24253
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell-derived interleukin-17A causes multiorgan dysfunction after hepatic ischemia and reperfusion injury

Abstract: Hepatic ischemia and reperfusion (IR) injury is a major clinical problem that leads to frequent extrahepatic complications including intestinal dysfunction and acute kidney injury (AKI). In this study we aimed to determine the mechanisms of hepatic IR-induced extrahepatic organ dysfunction. Mice subjected to 60 minutes of hepatic IR not only developed severe hepatic injury but also developed significant AKI and small intestinal injury. Hepatic IR induced small intestinal Paneth cell degranulation and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 36 publications
(58 reference statements)
1
80
0
5
Order By: Relevance
“…Both animal and human studies have indicated that hypoxia elicits tissue inflammation, so-called hypoxia-elicited inflammation (57)(58)(59)(60). Similarly, during inflammation, such as inflammatory bowel disease, the inflammatory organ becomes ischemic, so-called inflammatory hypoxia or inflammation-associated tissue hypoxia (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 98%
“…Both animal and human studies have indicated that hypoxia elicits tissue inflammation, so-called hypoxia-elicited inflammation (57)(58)(59)(60). Similarly, during inflammation, such as inflammatory bowel disease, the inflammatory organ becomes ischemic, so-called inflammatory hypoxia or inflammation-associated tissue hypoxia (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 98%
“…CD4+ T cells include not only Th1 and Th2 cells but also T helper 17 cells (Th17), Tregs and T follicular helper cells (Tfh). Previous studies have also shown that RAR-related orphan receptor gamma (RORγ)+IL-17+ neutrophils and IL-17A-producing natural killer cells play critical roles in a modified model of liver IRI, which occurred in RAG-deficient hosts [10]. Another study demonstrated that ex vivo-induced Treg cells could protect livers from IRI by inhibiting the activation of Kupffer cells in a liver partial warm ischemia model [11].…”
Section: Introductionmentioning
confidence: 99%
“…I n liver transplantation, organ exposure to ischemia and reperfusion during the transplantation process often leads to poor graft function; moreover, it may cause inflammatory activation in the intestine leading to multiorgan failure (1,2). Unfortunately, a lack of transplantable human livers has led to the usage of "marginal" organs at high-risk for severe ischemia reperfusion injury (IRI) (3).…”
mentioning
confidence: 99%